PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN - Sitompul, Clarisa Florentina (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to examine the influence of liquidity and profitability on company value with capital structure as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research uses a causal associative methodology related to quantitative data. The purposive sampling method was used to select the research sample, and 28 companies were selected during 5 years of observation so that the total sample in this study was 140 observations. The research results show that liquidity has no significant effect on company value (sig > 0.05). On the other hand, profitability is proven to have a significant positive influence on company value (sig < 0.05), indicating that increasing company profitability tends to increase company value. In addition, the moderation results show that capital structure does not moderate the relationship between liquidity and firm value (sig > 0.05). However, capital structure significantly moderates the relationship between profitability and firm value (sig < 0.05). This shows that capital structure can strengthen the influence of profitability on company value. Thus it can be concluded that liquidity does not have a significant influence on company value, either directly or when moderated by capital structure. On the other hand, profitability shows a significant positive influence on firm value, and this influence becomes stronger when moderated by capital structure. Keywords: Liquidity, Company Value, Profitability, Capital Structure.